A Report of Five Child Tetanus Cases - Boyarchuk, Oksana; Volyanska, Lubov; Synytska, Vira; Korytsky, Grygoriy; Burbela, Emilia (Journal of Pediatric Infectious Diseases, 2020)
We present five cases of generalized tetanus in children 5 to 13 years old, who were admitted to the intensive care unit of Ternopil Regional Children's Hospital (Western Ukraine) during the past 6 years (2012–2017). In our study, four children were unvaccinated and one received the full series of vaccinations. Proper vaccination in cases of infected wound may not prevent the development of the disease but improves the prognosis for recovery. Treatment of tetanus in Ukraine requires standardization of treatment protocols according to the World Health Organization recommendations, including making human tetanus immune globulin available, as specified by evidence-based medicine. Vaccines availability and education of physicians and parents about the benefits of immunization should be priority national health measures to prevent tetanus.
Keywords: tetanus; vaccines and immunization; Clostridium tetani